Facilitating Conditions and Social Influence on Zakat Payment Intention via QRIS: The Moderating Effect of Age at Baitul Mal Aceh - Fahri Zuan Ariga Sinaga; Ridwan Nurdin; Eka Nurlina (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2025)
This research examines how facilitating conditions and social influence affect individuals’ intentions to pay zakat via the QRIS platform, with age considered as a moderating variable in the setting of Baitul Mal Aceh. Anchored in the Unified Theory of Acceptance and Use of Technology (UTAUT), the study identifies the main factors driving the adoption of digital zakat payments. A quantitative approach was employed, using purposive sampling to gather data from 120 respondents. The dataset was analyzed through Structural Equation Modeling (SEM) using the Partial Least Squares (PLS) technique. Results show that both facilitating conditions and social influence have a significant and positive effect on the behavioral intention to adopt QRIS for zakat payments. Moreover, age functions as a moderator: younger participants are more responsive to facilitating conditions, whereas older individuals are more influenced by social pressure. These insights emphasize that successful implementation of QRIS in zakat collection depends on the interaction of enabling infrastructure, social dynamics, and generational differences factors that zakat management institutions should account for in policy and practice.